Brankas Rahasia: Media Pembelajaran Numerasi Berbasis Berpikir Komputasi untuk Meningkatkan Kemampuan Pemecahan Masalah - Umu Nasiba (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to improve the solving problems skills of Elementary School students in learning numeracy, using 'Brankas Rahasia' as learning media. This learning media is used to display numeracy questions attractively. Problem solving using computational thinking methods. This type of research is the development of the Hannafin and Peck model which consists of three steps, (1) needs analysis, (2) design, and (3) development. The data collection technique used was a written test. The data collection tool used is an online written test instrument. The data analysis used is quantitative data analysis. The results showed that the ‘Brankas Rahasia’ learning media can improve students' ability in abstracting skills (45%), generalization skills (65%), decomposition abilities (80%), and algorithm skills (95%). This shows that students' ability to solve problems by thinking computationally is good.